Comparison of PI3K Pathway in HPV‐Associated Oropharyngeal Cancer With and Without Tobacco Exposure. Issue 4 (9th August 2018) - Kiessling, Si‐Young; Broglie, Martina Anja; Soltermann, Alex; Huber, Gerhard Frank; Stoeckli, Sandro Johannes
Abstract : Objectives: The aim of the study was to evaluate whether HPV associated OPSCC with tobacco exposure follows a different carcinogenic pathway compared to HPV associated OPSCC without tobacco exposure and to investigate its prognostic significance. The question was addressed with focus on components of the PI3K pathway. Methods: 184 patients with newly diagnosed OPSCC treated with curative intent were consecutively enrolled. The expression level of p16, p53, PI3K, mTOR, and PTEN was assessed by immunohistochemistry and analyzed in relation to the risk factors HPV status and tobacco exposure. Results: 94 of 184 (51%) patients were p16 positive, p53 overexpression was detected in 48 of 184 (26%) cases. PI3K overexpression with 70 of 184 (38%) cases was significantly higher in p16 positive tumors. mTOR overexpression was present in 90 of 184 (49%) cases and significantly higher in p16 negative tumors. PTEN loss was found in 42 of 184 (23%) cases without association to p16 expression. p16 positive OPSCC showed lower rates of p53 expression and mTOR expression as well as higher rates of PI3K expression irrespective of tobacco exposure. Survival analysis showed a distinct intermediate survival rate of p16 positive smokers. The markers PI3K, mTOR, and PTEN did not have a significant impact on survival. Conclusion: HPV associated OPSCC with tobacco exposure follows the same expression level of the PI3K pathway as HPV associated OPSCC without tobacco exposure. The impaired survival rate of the intermediate risk group cannot be explained by different expression patterns of PI3K, mTOR, and PTEN. Level of Evidence: 2b